REFLECTION ON THE MINIMALIST LIFESTYLE AND ITS INFLUENCE ON MENTAL HEALTH AND FINANCIAL STABILITY: A STUDY AUTO ETHNOGRAPHYPOST-PANDEMIC STUDENTS - Lilis Karlina; Mardiana; Muhammad Fauzan (Indragiri Research Center (ingreat), 2024)
This research is a study auto ethnography. This article reflects the author's personal experience as a post-pandemic student facing the increasing consumer pressures brought on by the development of social media. In a digital era that promotes instant, aesthetic, and viral lifestyles, students find themselves caught in a vortex of social standards shaped by algorithms and digital imagery. Through a reflective narrative, the author illustrates how choosing a minimalist lifestyle is not only a financial decision but also a strategy for maintaining mental health. This research confirms that impulsive consumption often stems from emotional impulses and digital social pressures, rather than real needs. Therefore, contextual consumption literacy is needed that can equip the younger generation with awareness, resistance to visual influences, and the ability to organize life priorities. The results of this study are expected to contribute to the development of financial literacy and mental health based on real experiences.